PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI, DIMEDIASI MOTIVASI KERJA - Solikhin, Solikhin; Purwani, Tri; Erbito, Yoseph; Marwati , Sri (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
This research aims to determine the influence of the transformational leadership and physical work environment on employee performance with work motivation as a Mediating Variable at Dinas Koperasi Usaha Kecil Dan Menengah, Perindustrian Dan Perdagangan yang ada di Kab. Bantul This research design is quantitative research with a population of 122 employees anda sample of 122 respondents. The data collection method in this research uses the questionnaire method. Data analysis used in this research uses a Structural Equation Model(SEM) approach based on Partial Least Square (PLS). The results of this research show that the Transformational leadership has a positive influence on performance, transformational leadership has a positive influence on work motivation, the physical work environment does not affect performance, the physical work environment has a positive influence on work motivation, work motivation has a positive influence on performance, there is a positive relationship between transformational leadership and performance mediated by work motivation, there is a positive relationship between the physical work environment and performance, mediated by work motivation.